Development of a sensitive passive sampler using indigotrisulfonate for the determination of tropospheric ozone - Garcia, Gabriel [UNESP]; Allen, Andrew George [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Royal Soc Chemistry, 2010)
A new sampling and analytical design for measurement of ambient ozone is presented. The procedure is based on ozone absorption and decoloration (at 600 nm) of indigotrisulfonate dye, where ozone adds itself across the carbon-carbon double bond of the indigo. A mean relative standard deviation of 8.6% was obtained using samplers exposed in triplicate, and a correlation coefficient (r) of 0.957 was achieved in parallel measurements using the samplers and a commercial UV ozone instrument. The devices were evaluated in a measurement campaign, mapping spatial and temporal trends of ozone concentrations in a region of southeast Brazil strongly influenced by seasonal agricultural biomass burning, with associated emissions of ozone precursors. Ozone concentrations were highest in rural areas and lowest at an urban site, due to formation during downwind transport and short-term depletion due to titration with nitric oxide. Ozone concentrations showed strong seasonal trends, due to the influences of precursor emissions, relative humidity and solar radiation intensity. Advantages of the technique include ease and speed of use, the ready availability of components, and excellent sensitivity. Achievable temporal resolution of ozone concentrations is 8 hours at an ambient ozone concentration of 3.8 ppb, or 2 hours at a concentration of 15.2 ppb.